Cartilagem auricular de bovinos tratada com solução alcalina: avaliação histológica pré- implantação e termográfica pós-implantação na parede abdominal de coelhos (Oryctolagus cuniculus) - Ferreira, Kamilla Dias (2017)
This study aimed to evaluate the viability of the decellularization process in bovine cartilaginous tissue by histological analysis. For this purpose, 20 bovine elastic cartilages were used, immersed in alkaline solution for 72 hours, followed by washing, freezing and lyophilization of the material. Histological processing was then performed to perform the analyzes. In the histological analyzes the decellularization and removal of the amorphous substance from the tissue was observed, but the structure of elastic fibers and collagen remained. It was concluded that the alkaline treatment was efficient to obtain biomaterial from elastic cartilaginous tissue. This study also evaluated, through thermographic examination, the feasibility of using implants with biomaterials obtained from elastic cartilages treated in alkaline solution. The intensity of the inflammatory process was observed through the variation of cutaneous temperature comparing before and after the implantation of the biomaterials in rabbits (Oryctolagus cuniculus). A total of 24 rabbits were evaluated, divided into two groups, of 12 animals each, according to the implanted biomaterial. Evaluations were performed in the preoperative period and after the implantation of biomaterials. In the (GI) group, polypropylene mesh and elastic cartilage (GII) were treated with alkaline solution, evaluated in the periods of seven and 35 days. From the results obtained, after performing statistical tests, the group (GI) polypropylene mesh, obtained upper abdominal skin temperatures, compared to the cartilage group, providing subsidies that the use of elastic cartilage treated in alkaline solution, promoted lower inflammatory intensity due to the processing to which it was submitted. It is concluded that treated elastic cartilage has been shown to be a superior biomaterial relative to the mesh polypropylene.